Adaptive sport as real alternative for improving lives of people with disabilities - Slukhenska, Ruslana Vasylivna (Journal of Education, Health and Sport, 2018)
The article examines adaptive sport as alternative for improving lives of people with disabilities. Domestic and foreign experience of working with disable people have shown that physical education and sport are the most efficient methods of rehabilitation among mentioned contingent. Sanative physical education and adaptive sport generally allow realizing possibilities of people’s organism for full life, self-realization, social activity and integration into society, with the help of rationally organized motor activity as natural incentive of livelihoods, using preserved functions, remaining health, natural sources, and mental forces. Aim of the article is to consider main characteristics of sanative physical education as kind of active activity, define its aims, functions, theoretical principles and efficient realization on the practice. The article uses the following research methods: abstraction and generalization, induction. Conclusions. Sanative physical education and adaptive sport generally allow realizing possibilities of people’s organism for full life, self-realization, social activity and integration into society, with the help of rationally organized motor activity as natural incentive of livelihoods, using preserved functions, remaining health, natural sources, and mental forces.